Efektifitas Metode Ilman Wa Ruuhan Pada Pembelajaran Aqidah Akhlak di SDIT Bintangku Probolinggo - Mardiana Mardiana; M. Jadid Khadavi (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study aims to examine the implementation of the Ilman wa Ruuhan method in Aqidah and Akhlak learning at SDIT Bintangku Probolinggo. The method is an integrated approach that combines cognitive (ilman) and spiritual (ruuhan) aspects to holistically shape students’ Islamic character. The focus of this research goes beyond technical skills in reading and memorizing the Qur’an, emphasizing the internalization of faith, moral values, and daily Islamic manners. This study employs a descriptive qualitative approach using data collection techniques such as observation, interviews, and documentation. The findings show that the Ilman wa Ruuhan method is implemented gradually through socialization, teacher training, classroom practice, and regular evaluations based on students’ behavioral changes. Although various methods for teaching Aqidah and Akhlak have been implemented in elementary schools, many of them have not been able to consistently instill Islamic values and develop noble character in students. In addition, studies on the effectiveness of the Ilman wa Ruuhan method at the SDIT level are still limited and have not been extensively explored, thereby creating a gap that needs to be addressed. Based on this gap, the present study emphasizes that the Ilman wa Ruuhan method has been proven to improve students’ understanding of Islamic values, discipline, and behaviors that reflect noble character. Support from teachers, students, and parents serves as an important factor contributing to its successful implementation. Thus, the Ilman wa Ruuhan method is effective for teaching Aqidah and Akhlak and has the potential to become a model for Islamic character education at the elementary school level.